2021
DOI: 10.9734/jpri/2021/v33i48a33226
|View full text |Cite
|
Sign up to set email alerts
|

The Awareness and Attitudes of the Public toward Complementary and Alternative Treatments

Abstract: Introduction: Complementary and alternative medicine (CAM) is flourishing very fast and the usage of CAM in health care is quickly evolving. The behavior and attitude of the patients towards herbal medicines represents an important concern for policy makers and for regulators. Objective: The aim of this study is to evaluate the pattern of natural products use among the public and the Attitudes towards natural health products in Al-kharj Methodology: This is a cross-sectional study design. A questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In addition, they noted that regarding diagnosis, more than 89% of respondents claimed they preferred taking advice from real doctors. [20] Ahmed et al reported that a significant portion of the public distrusts the deployment of AI because they believe it could make deadly mistakes. [20]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, they noted that regarding diagnosis, more than 89% of respondents claimed they preferred taking advice from real doctors. [20] Ahmed et al reported that a significant portion of the public distrusts the deployment of AI because they believe it could make deadly mistakes. [20]…”
Section: Discussionmentioning
confidence: 99%
“…[20] Ahmed et al reported that a significant portion of the public distrusts the deployment of AI because they believe it could make deadly mistakes. [20]…”
Section: Discussionmentioning
confidence: 99%